Fatigue design curves of materials collected from old portuguese metallic bridges - Cardani, Marian (2017)
This paper aims to extend the interpretation of data collected from experimental tests developed to analyse the fatigue phenomena on the material obtained from old Portuguese metallic bridges. The metallic bridges addressed were built in the late nineteenth and early twentieth centuries and have now become important historical heritage. The main materials used at that time were steel and puddle iron. The analysis of the results is made following the statistical models proposed in actual codes.